PENGARUH BERBAGAI MEDIA DAN INOKULAN MIKORIZA TERHADAP PERTUMBUHAN BIBIT ANGGREK Phalaenopsis sp HASIL KULTUR JARINGAN - kusmawati, eni; Listiawati, Agustina; Rahayu, Sri (Jurnal Sains Pertanian Equator, 2015)
Phalaenopsis sp has attracted a lot of people due to the beauty of its shape and colorful flower. Media was needed to seed this orchid, in this research, is easy to find; for example moss, fern, kadaka, and coconut coir. The use of mycorrhizal was beneficial for the orchid growth. The purpose of this research was to obtain the best result in the provision of mycorrhizal inoculants and get the various of media that is the best for the growth of Phalaenopsis sp seed. The research was conducted on the sample terrain of Agriculture Faculty Universitas Tanjungpura. This research used two factors Complete Randomized Design (RAL). The first factors is the m1: fern; m2: moss; m3: kadaka; and m4: coconut coir. The second factors were two degree of mycorrhizal inoculants; k0: without inoculant, k1: 100g of mycorrhizal inoculant. The parameters observed were percentage of survived plants, number of leaves increase, leaves width increase, leaves lenght increase leaves clorofile, number of roots, roots length, and percentage of infected roots. The research results showed that mycorrhizal inoculant given apparent result towards the leaves width increase, leaves lenght increase, leaves clorofile, number of roots, roots length, and percentage of infected roots, the use of media given apparent results towards roots length and leaves clorofile variable. Media treatment and mycorrhizal inoculants that there are no interaction of all the variables of observation. The best result given by moss media, having the best average variables in number of roots, roots length, and percentage of infected roots.Keywords: inoculant, mycorrhizal, media, Phalaenopsis sp